DISTANCE LEARNING FOR HEALTH CARE PROFESSIONALS – CHALLENGES, OPPORTUNITIES AND SOLUTIONS - Avota, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The research was done in the framework of internal scientific project grant of Riga Medical College of the University of Latvia. The study took place between 01.04.2016.- 01.11.2016. Aim of the research. To evaluate feasibility and necessity for further education courses for medical personnel in form of distance learning and to assess the newly developed distance learning course methodological material for continuing education. Methodology: quantitative – 2 surveys, where the results apply to the focus group only. Results. There is a low supply of vocational further education in medicine in form of distance learning and the majority - 61% of nurses and physician assistants have never used such materials, while 77% of respondents acknowledge that distance learning is necessary. The main barriers, interfering with successful learning according to 33% of respondents are lack of time and 28% lack of self-motivation. Distance learning materials, are very interesting and of high quality, as the respondents evaluated with 5 and 6 points (in 6-point scale). Conclusion. Distance learning is needed not only for broadening the supply, but the necessity is also determined by the demand, which is attributed to the time and financial savings.